'Objective Reasonableness' as a Standard for International Judicial Review. (27th July 2015) - Tully, Stephen R.
Abstract: In Whaling in the Antarctic (Australia v Japan, New Zealand intervening), the International Court of Justice concluded that the design and implementation of Japan's whaling programme was not reasonable in relation to achieving its stated objectives. The Court posited a test of objective reasonableness as the applicable standard of review. This article contends that this standard is not and should not be a regular feature of dispute settlement by that Court. Like the margin of appreciation doctrine, an objective reasonableness test is a mechanism for demonstrating judicial deference. However, such a test merely substitutes the subjective intentions of litigants with judicial subjectivity. For the Court to employ this standard of review would subvert its judicial function, exceed authority and take it beyond its expertise. The judgment is distinguishable on its facts, in its terms and by reference to the parties' submissions. The approach should not be used to resolve future disputes.